Network performance and security : testing and analyzing using open source and low-cost tools - Chapman, Chris (Elsevier Ltd., 2016)
Providing mid-level IT engineers with the practical tips and tricks they need to harden their IT infrastructure, this book shows how to use open source tools to test network configurations for malware attacks, DDoS, botnet, rootkit and worm attacks, and includes tactics on how to prepare and execute a mediation schedule of the who, what, where, when, and how, when an attack hits. --